Parental Compassion in Family Education from the Perspective of Hadith and Its Implications for Children’s Mental Health - Ahmad Komarudin; Maslani Maslani; Yulida Fauziyah; Lukmanul Hakim; M. Iqbal Gelar Budiman (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study explores the concept of compassion (al-rahmah) in family education based on prophetic hadiths and examines its contribution to childrens mental health. Using a qualitative method with a library research approach, this study analyzes primary hadith sources, classical commentaries, and contemporary psychological literature. The findings identify seven core hadiths that emphasize compassion, gentleness (rifq), physical expressions of affection, age-appropriate moral training, and responsible family leadership (kullukum rain) as fundamental elements of Islamic educational ethics. Interpretations by classical scholars such as An-Nawawi, Al-Ghazali, and Ibn Qayyim demonstrate that compassion is not only a moral virtue but also a structured educational strategy that aligns with modern mental health theories. Compassionate family practices positively influence childrens emotional security, stress regulation, empathy, self-confidence, and long-term psychological resilience. Conversely, a lack of affection increases vulnerability to anxiety, emotional dysregulation, and mental health risks in adulthood. Therefore, family education grounded in Islamic compassion serves as both a religious mandate and a strategic psychological investment to develop mentally healthy, emotionally balanced, and resilient future generations.